Exploring How Gender and Sex Are Measured in Criminology and Victimology: Are we Measuring What we Say we Are Measuring?. Issue 1 (4th March 2022) - Crittenden, Courtney A.; Gateley, Hannah C.; Policastro, Christina N.; McGuffee, Karen
Abstract: Throughout the years, there have been sustained and increasing calls for criminology to become more inclusive in its research and measurements with the purpose of improving our knowledge of crime and victimization. The current study examined articles published in the past five years in a mainstream criminological journal and a well-respected victimization journal to explore the inclusion and operationalization of gender and sex. Findings indicate that measures of gender and sex were included more in the diversity-focused victimization journal compared to the mainstream criminological journal. In both journals, however, conceptualizations and operationalizations of these constructs rarely fell outside of a binary measure, which suggests the measurement and inclusion of gender are still lacking, and oftentimes when we say we are measuring gender we are actually still measuring sex.